2018
DOI: 10.1021/acsami.8b07993
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Complementary in Absorption Spectra with Fullerene, Nonfullerene Acceptors and Medium Band Gap Donor for High-Performance Ternary Polymer Solar Cells

Abstract: Because of the mismatch between the solar irradiance spectra and the photoactive layer absorption spectra, only a part of sunlight can be utilized, which fundamentally restricting the power conversion efficiency (PCE) of the polymer solar cells (PSCs). Ternary blend PSCs, with an additional third component, have become an effective approach to extend the absorption spectra and increase the mobility of the charge carriers. Herein, we select the middle band gap PBDTBDD as an electron donor and narrow band gap IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…The transient photoluminescence (PL) measurement can monitor the charge transfer by using a selected wavelength to excite one component and to probe its PL emission intensity. After blending with the other component (cannot be excited in this wavelength), the shorter PL intensity lifetime indicates effective charge transfer occur 67,90 but the longer PL intensity lifetime may mean the existence of energy transfer.58 In addition to transient PL measurement, the transient absorption (TA) spectroscopy can also investigate charge transfer and combination dynamics by monitoring ground-state bleaching and photo-induced polarons. 72,[91][92][93] As for the PBDB-T: ITIC binary OPV, it is found that the excitons generated in ITIC would separate at the PBDB-T/ITIC interface, then the electrons and holes would transfer to the cathode and the PBDB-T, respectively.…”
Section: Mending Charge Dynamicsmentioning
confidence: 99%
“…The transient photoluminescence (PL) measurement can monitor the charge transfer by using a selected wavelength to excite one component and to probe its PL emission intensity. After blending with the other component (cannot be excited in this wavelength), the shorter PL intensity lifetime indicates effective charge transfer occur 67,90 but the longer PL intensity lifetime may mean the existence of energy transfer.58 In addition to transient PL measurement, the transient absorption (TA) spectroscopy can also investigate charge transfer and combination dynamics by monitoring ground-state bleaching and photo-induced polarons. 72,[91][92][93] As for the PBDB-T: ITIC binary OPV, it is found that the excitons generated in ITIC would separate at the PBDB-T/ITIC interface, then the electrons and holes would transfer to the cathode and the PBDB-T, respectively.…”
Section: Mending Charge Dynamicsmentioning
confidence: 99%
“…Compared with conventional fullerene derivatives acceptors, non-fullerene acceptors have diversified and strong absorption, so they are the better options to introduce into the traditional system as the third component [18]. For example, Tan et al developed a ternary acceptor blending device by doping 3,9-bis(2-methylene-(3-(1,1dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3d:2,3′-d′]-s-indaceno[1,2-b:5,6-b′]dithiophene (ITIC) in the PBDTBDD:PC 60 BM blend to achieve perfect complementary absorption and high PCE of 10.36% [19]. Furthermore, the distinctive feature of ITIC is the long-wave spectral response of 600–800 nm, compared with the short and medium wave response inherent in traditional fullerene derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28] In ternary OSCs, expanding the absorption coverage by adding a third component with complementary light absorption can lead to a great enhancement in short-circuit current density (J sc ). [29][30][31][32][33][34][35][36][37] Meanwhile, a higher open-circuit voltage (V oc ) can be realized through modulating the energy levels by introducing a high lowest unoccupied molecule orbital (LUMO) acceptor or deep highest occupied molecule orbital (HOMO) donor or a third component with low energy loss in ternary OSCs. [18,[38][39][40][41][42][43][44][45][46] However, controlling the fill factor (FF) is less straightforward because it depends on multiple factors, such as charge recombination, charge transport, interfaces, and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, the strategy of a ternary blend consisting of either two donors and one acceptor or one donor and two acceptors has been widely applied to elevate the PCEs of OSCs via overcoming one or more of the aforementioned limitations . In ternary OSCs, expanding the absorption coverage by adding a third component with complementary light absorption can lead to a great enhancement in short‐circuit current density ( J sc ) . Meanwhile, a higher open‐circuit voltage ( V oc ) can be realized through modulating the energy levels by introducing a high lowest unoccupied molecule orbital (LUMO) acceptor or deep highest occupied molecule orbital (HOMO) donor or a third component with low energy loss in ternary OSCs .…”
Section: Introductionmentioning
confidence: 99%